The Effect of Educational Intervention Based on PRECEDE-PROCEED Model on the Life Quality of Women-Headed Households Covered By Tehran Welfare Organization - Mahnaz Solhi; Marzieh Shabani Hamedan; Masoud Salehi (Iranian Association of Health Education and Health Promotion, 2017)
Background and objective: The women-headed households are more susceptible to social damages than other women. Such condition remarkably influences the women's health-related life quality. The present study was aimed to investigate the effect of the educational intervention based on PRECEDE-PROCEED model on the quality of life in women-headed households covered by the Tehran Welfare Organization. Materials and methods: About 180 household-head women, from among the women under the protection of Tehran Welfare Organization, participated in this quasi experimental witnessed study. Sampling was done through multistage random sampling method. Instruments used for gathering data included life quality standard questionnaire (WHOQOL-BREF) and a researcher-made questionnaire about the structures of ecologic and educational diagnosis phase of the PRECEDE-PROCEED model whose validity and reliability were approved in the primary study. Based on the results obtained from the primary filling of the questionnaire, the appropriate educational intervention was designed and performed in the case group. One month and three months after the intervention, data were analyzed by SPSS 15 using the descriptive (the mean, SD, frequency and percentage) and analytical tests (t, Mann-Whitney, Chi Square, ANOVA with repeated measures, and Freedman tests). Results: Before intervention no significant difference was observed between the mean scores of the life quality, behavioral factors, and knowledge, enabling, and reinforcing factors among the two groups. But one month and three months after intervention a significant difference was observed between the mean score of the life quality (p = 0.001), behavioral factors (p = 0.001), and knowledge (p = 0.001), enabling (p < 0.001), and reinforcing factors (p = 0.001) in the two groups. Conclusion: Educational intervention through the PRECEDE-PROCEED model effects the women-headed households' quality of life improvement.